Subclinical Hypothyroidism in Families Due to Chronic Consumption of Nitrate-Contaminated Water in Rural Areas with Intensive Livestock and Agricultural Practices in Durango, Mexico - García-Torres, Edgar; Pérez-Morales, Rebeca; González-Zamora, Alberto; Calleros-Rincón, Esperanza Yasmín (Water (Basel), 2022)
Nitrate is a widely disseminated water pollutant and has been linked to health disorders, including hypothyroidism. Here, we evaluated the relationship between thyroid function and chronic exposure to nitrates in rural zone families, in addition to the genetic and autoimmune factors. Exposure and effect biomarkers, thyroid hormones, and autoantibodies of tiroperoxidase were measured, as well the presence of two FOXE1 polymorphisms (rs965513, rs1867277). Pearson’s correlation, principal component analysis, Kruskal–Wallis, and chi-squared tests were used for statistical analysis. A total of 102 individuals were analyzed; 45% presented subclinical hypothyroidism, a negative correlation was observed between methemoglobin and the total T3 (r = −0.43, p = 0.001) and free T3 levels (r = −0.34, p = 0.001), as well as between TSH and the free T4 (r = −0.41, p = 0.0001) and total T4 (r = −0.36, p = 0.0001). A total of 15.7% had positive antithyroid ab-TPO, while the polymorphic genotype (AA) represented only 3% (rs965513) and 4% (rs1867277) among subjects with subclinical hypothyroidism. The high frequency of subclinical hypothyroidism in the population under study could be related, mainly, to chronic exposure through the consumption of nitrate-contaminated water.